Easy pass (EZPA) - Ainuddin Zaidee, Nur Syamimi Asyranee; Join, Tiara; Shaiful Nizam, Nurizz Eireen; Zalzala, Nurain Najwa; M Said, Salasiah (Universiti Teknologi MARA, Kedah, 2018)
EZPA is a system that develops the access key to almost all of the information agencies such as libraries and archive. The new RFID technology needs to be access via a card that link to the new security system. EZPA functions as security/ access pass to enter a building. It is more than just a security/ access pass, it is developed with built in RFID in it. How it works?. EZPA will be scan at the entrance and exit door. It works strictly where one with EZPA only will be allowed to enter the building. Furthermore, EZPA will help with the user statistics of the information agencies and it will help in the restricted areas such as archive restricted area. This EZPA only required RFID tag and RFID scanner/reader at the entrance and exit door. Novelty and uniqueness:  Automatically scan  Improve the security using RFID code